Foodpanda’s Impact on Consumer Behavior During the Pandemic - Hui Jun Ang; Alwenna Fabian Jules; Aina Zalikha Zulhaime; Xiao Sian Ang; Amir Aiman Kamarozaman; Natalia Pontoh (AIBPM Publisher, 2022)
The COVID-19 pandemic has set off a new era in the world, the food delivery applications have become an important aspect of individuals’ daily lives. In addition, consumer behavior will change during COVID-19 pandemics. Due to changes in consumer behavior during the pandemics, many companies are facing difficulties such as reduced sales. Therefore, this paper aims to examine the impact of consumer behavior on Foodpanda during the COVID-19 pandemic. Lockdown and social distancing have disrupted consumer buying and shopping habits during the COVID-19 pandemic. This dramatic scenario also strongly influenced consumer behavior. The data was collected using an online questionnaire. The data was collected primarily through surveys distributed to 100 respondents. The results show that Food panda provides a very convenient service for customers during the Covid-19 outbreak. The results also show that customers are satisfied with the quality of Food panda’s service. Keywords: Consumer Behavior, Covid-19 Pandemics, Food Panda, Impact.